Physical Activity Levels And Junk Food Intake Among School Going Adolescents In A North Indian City - Ahmad, Sameena; Ansari, M Athar; Abedi, Ali J; Khalil, Salman; Eram, Uzma; Khan, Najmul A (Indian Journal of Community Health, 2023)
Introduction: Physical activity and diet go hand in hand for the maintenance of good health. This becomes even more important in school-going adolescent students as they are readily exposed to a wide variety of junk food items inside or around their school premises and lead increasingly sedentary lifestyles as they progress through their academics. Aim and Objective: Toassess the junk food intake and physical activity level among school-going adolescents. Material and Method: This cross-sectional study was conducted among 800 school-based adolescents aged 12 to 14 years at AMU High Schools, Aligarh. Students were asked about their physical activity and dietary habits by disseminating a self-reported questionnaire. The data were analyzed in SPSS version 20.0. Results: The majority of the adolescents had a moderate level of physical activity (53%), while 23% of the students had high and 24% had low physical activity levels. On the analysis of the students’ dietary habits, it was found that a staggering 70.75% of students had more than the recommended intake of junk food items. The association between physical activity and junk food intake was found to be significant. Conclusion: More emphasis should be given to limiting junk food intake, increasing healthy food intake, and motivating the students to be more physically active. This can be done by encouraging the family as well as teachers at the school level and creating more spaces for children to be physically active at the community level.